Relaxation training to reduce the parenting stress of mother of preschool age children - Yasmin Meutia Solihati (Universitas Pendidikan Ganesha, 2020)
Parenting stress was experienced by all mothers, especially mothers who had preschool-age children. Parenting stress experienced by the mother would affect the confidence and perception of the mother towards care so that it affected the child's development and family stability. This research aimed to examine the effectiveness of relaxation training in reducing parenting stress of mothers for preschool-age children. Five mothers of preschool children participated in this research. The measuring instrument used was the parenting stress index, with a one-group pretest-posttest design research design. The results showed that relaxation training was significantly proven to reduce the stress of parenting in preschool children. The participants expressed that they felt more relaxed and calm so that they were able to manage emotions and find alternative solutions when facing problems that caused the emergence of parenting stress. Besides, physical tension felt to be more reduced.